Research and innovation 2018 - Vaz, Filipe; Pereira, Guilherme (UMinho Editora, 2020)
The University of Minho (UMinho) defined some years ago a comprehensive and integrative research policy in order to actively contribute to pushing the frontiers of human knowledge, to the reinforcement of the national scientific system, and to the consolidation of its institutional position both in national and international arenas. Thus, the commitment to become a research university is stated in the different strategic documents approved by the University along the last decade. UMinho defined a clear strategy in order to be an open and permanent space for the creation of knowledge and the furtherance of nationally and internationally relevant innovation across the different areas of knowledge. Being a comprehensive University, UMinho aims at fostering high quality research in all the scientific domains in which our Research Units inscribe their activity: Sciences, Health and Life Sciences, Engineering and Technology, Social Sciences and Arts and Humanities. From the very beginning, UMinho has adopted the principles of open access and open science. We aim at carrying out our scientific activity in a transparent and collaborative way, actively promoting the sharing and communication of research processes, data and outputs. We are convinced that we do better science when we make it both more sensitive to the needs of society and also more effective in what concerns the allocated resources. As we see it, accountability is a pre-requisite for reinforcing citizen awareness of the contributions of science to a better world. These are the reasons why UMinho played a pioneering role in allowing open access to its publications and why it is currently expanding its sharing of research data. At UMinho, research is carried out in close connection with education. The University is increasingly involving students of the different learning cycles in research activities. Conversely, both PhD students and post-doctoral researchers play a role in teaching activities. Acting in this way, not only do we guarantee better quality education but we also establish the basis for a sustainable development of the scientific system and the fostering of scientific culture. We conceive research as a global enterprise, seeking for the answers to the main challenges of our times. In this sense, research is essentially international and requires the continuous reinforcement of international collaborations and participation in international initiatives, namely in the context of the European Research Area. At the same time, we are always promoting the multiplier effects of the scientific research we undertake for the socio-economic and cultural development of the country and of our region. The University's high-quality scientific performance is clear when we consider: (i) the results of the international evaluation of our Research Units carried out by the National Science Foundation (FCT); (ii) the position that UMinho has been achieving in important international rankings; (iii) the number and diversity of University projects approved under the 7th Framework Program and the H2020; and (iv) the large collaboration projects with companies and other organisations that are under development. The high standards of the activity of our Research Units is made clear in this publication. When we consider the characteristics of their human resources, their publications, the projects funded by national and international agencies, the national and international recognition of their researchers, the networks with which they are engaged, and the scientific events they promote it becomes clear how well positioned in the national and international context our Research Units are. This publication gives a general overview of research in UMinho along the year of 2018. It is the first of a series providing detailed information about the research work of the University. Research at UMinho is governed by a permanent concern with providing feedback to the scientific community and to our fellow citizens as most of our funding is from public sources. Together with the adoption of external evaluation procedures, providing feedback is one of the best ways to establish the relevance of science undertaken for the public good, and for guaranteeing the scientific independence of our researchers and their Research Units. Nowadays, science is essential for fostering social and economic development. Through this publication we reveal the relevant role that UMinho is playing in this enterprise. Rui Vieira de Castro Rector